Synthesis, structural elucidation and X-ray crystallographic studies of 1-(3,5-bis(trifluoromethyl)phenyl)-3-(dimethylamino)prop-2-en-1-one - Nongrum, Stability; Das, Susma; Khanikar, Shikpika; Vishwakarma, Jai Narain (European Journal of Chemistry, 2019)
A new enaminone was synthesized by reacting 3,5-bis-(trifluoromethyl)acetophenones and N,N-dimethylformamide dimethyl acetal and its detailed structural and crystalline properties were studied. The crystal data were found to be as C13H11F6NO, monoclinic, space group P21/c (no. 14), a = 8.1556(8) Å, b = 24.877(3) Å, c = 7.6067(7) Å, β = 116.745(6)°, V = 1378.2(3) Å3, Z = 4, T = 293(2) K, μ(MoKα) = 0.150 mm-1, Dcalc = 1.500 g/cm3, 40777 reflections measured (5.594° ≤ 2Θ ≤ 56.786°), 3413 unique (Rint = 0.1040, Rsigma = 0.0584) which were used in all calculations. The final R1 was 0.0771 (I > 2σ(I)) and wR2 was 0.2541 (all data).